Temporomandibular disorders : a problem-based approach - Gray, Robin J. M.; Al-Ani, M. Ziad. (Hoboken : John Wiley & Sons, 2011)
A quick, systematic and logical approach to diagnosing and treating temporomandibular disorders (TMD), this latest book in the Dental Update series is an essential clinical companion for dental students and practising dentists. Starting with an overview of the basic principles of TMD, such as the anatomy of the temporomandibular joint and its physiology and pathology in relation to clinical treatment, the book goes on to present the realities of managing patients, using a case-based approach to help readers understand and engage with the information. Each later chapter presents a different pro.
Chapter 14 What's of Use to Me in Practice?Chapter 15 You and the Lawyer; Chapter 16 The Referral Letter; Chapter 17 How to Make a Splint; Chapter 18 Patient Information; Chapter 19 Glossary of Terms; Chapter 20 Short Answer Questions; Index.
Print version record.
Keywords: Temporomandibular joint -- Diseases; Temporomandibular Joint Disorders -- diagnosis; Temporomandibular Joint Disorders -- therapy; Temporomandibular Joint -- physiopathology; Medicine; Electronic books